Pengaruh Kualitas Pelayanan dan Promosi terhadap Keputusan Pembelian Sepeda Motor Yamaha pada PT Arista Garut - Tatang Mulyana (Fakultas Ekonomi Universitas Garut, 2016)
The purpose of this study was to determine the effect of service quality and promotion on purchasing decisions at PT. Arista Garut. The method in this research is using associative descriptive analysis method. The respondents in this study were 96 respondents, with certain criteria using incidental sampling techniques. Data analysis techniques to determine the effect of service quality, promotion and purchase decisions using multiple linear regression analysis with simultaneous and partial testing. The result of the research states that simultaneously there is an influence of service quality and promotion on purchasing decisions, meaning that consumers consider the quality of service and promotion in deciding to make a purchase and partially there is an influence of service quality on purchasing decisions at PT. Arista Garut and there is a promotional effect on purchasing decisions at PT. Arista Garut. The conclusion of this research is that service quality is considered good and plays a role in consumer purchasing decisions and promotions are considered good and plays a role in consumer purchasing decisions at PT. Arista Garut to decide to make a purchase.